Residual symptoms and specific functional impairments in euthymic patients with bipolar disorder. (6th March 2016) - Samalin, Ludovic; de Chazeron, Ingrid; Vieta, Eduard; Bellivier, Frank; Llorca, Pierre‐Michel
Abstract : Objectives: The aims of the present study were to confirm the impact of residual symptoms on overall functioning in a large sample of euthymic patients with bipolar disorder in real‐life conditions and to explore the relationship between residual symptoms and specific areas of functional impairment. Methods: This was a multicenter, cross‐sectional, non‐interventional study of euthymic outpatients with bipolar disorder. The Functioning Assessment Short Test was used to assess overall and specific domains of functioning (autonomy, occupational functioning, cognitive functioning, financial issues, interpersonal relationships, and leisure time). Various residual symptoms were assessed (residual mood symptoms, emotional dysregulation, sleep and sexual disorders, stigma, and perceived cognitive impairment). Logistic regression was used to determine the best model of association between functional domains and residual symptoms. Results: Almost half of the 468 patients included (42%) had poor overall functioning. Residual depressive symptoms appeared to have an impact on overall functioning and in nearly all areas of functioning. In addition, specific residual symptoms had significantly more negative effects on some domains of functioning in euthymic patients with bipolar disorder (residual manic symptoms and occupational stigma on autonomy, emotional inhibition on occupational functioning, residual manic symptoms on financial issues, family stigma on interpersonal relationships, and sexual function and occupational stigma on leisure time). Conclusions: Our findings highlight the importance of evaluating overall functioning in clinical practice as well as functional domains. They also indicate that some residuals symptoms in patients with bipolar disorder should be targeted in personalized treatment plans, in order to improve functioning in the domains in which the patient is most impaired.